The effects of periodized resistance training on the neuromuscular performance, body composition and balance control among older and young adults - Manlangit, Pastor Jr (2019)
Strength, power and muscle mass decline with age. These declines lead to poorer balance and increased risk for falls. Intervention studies using a periodized resistance training (RT) among the older are limited, despite its widespread applications in fitness and sports among young adults. In addition, the effects of periodized RT on balance control remain to be investigated. This study sought to examine the effects of a short term periodized RT on the neuromuscular performance, body composition and balance control among older and young adults.